Fluoxetine Protects Retinal Ischemic Damage in Mice - Giovanni Luca Romano; Lucia Gozzo; Oriana Maria Maurel; Serena Di Martino; Valentina Riolo; Vincenzo Micale; Filippo Drago; Claudio Bucolo (MDPI AG, 2023)
Background: To evaluate the neuroprotective effect of the topical ocular administration of fluoxetine (FLX) in a mouse model of acute retinal damage. Methods: Ocular ischemia/reperfusion (I/R) injury in C57BL/6J mice was used to elicit retinal damage. Mice were divided into three groups: control group, I/R group, and I/R group treated with topical FLX. A pattern electroretinogram (PERG) was used as a sensitive measure of retinal ganglion cell (RGC) function. Finally, we analyzed the retinal mRNA expression of inflammatory markers (IL-6, TNF-α, Iba-1, IL-1β, and S100β) through Digital Droplet PCR. Results: PERG amplitude values were significantly (p < 0.05) higher in the I/R-FLX group compared to the I/R group, whereas PERG latency values were significantly (p < 0.05) reduced in I/R-FLX-treated mice compared to the I/R group. Retinal inflammatory markers increased significantly (p < 0.05) after I/R injury. FLX treatment was able to significantly (p < 0.05) attenuate the expression of inflammatory markers after I/R damage. Conclusions: Topical treatment with FLX was effective in counteracting the damage of RGCs and preserving retinal function. Moreover, FLX treatment attenuates the production of pro-inflammatory molecules elicited by retinal I/R damage. Further studies need to be performed to support the use of FLX as neuroprotective agent in retinal degenerative diseases.